(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe D-dimer concentrations and analyze factors related to hypercoagulability in post-Covid-19 patients at Dai Phuoc General Clinic. Subject and method: Retrospectively performed records of 457 patients who had been infected with Covid-19 and had results of quantification of D-dimer concentrations at Dai Phuoc General Clinic from June to July 2022. Results: 371/457 subjects (81.2%) had D-dimer concentrations < 500 ng/mL and 86/457 subjects had D-dimer concentrations ≥ 500 ng/mL (18.8%). The women have higher D-dimer concentrations than men (z = 5.037, p (sig. (2-sided test)) < 0.05). Patients ≥ 60 years old had higher D-dimer concentrations than those under 60 years old (z = 7,243, p (sig (2-sided test)) < 0.05). Patients with medical conditions were also reported to have higher D-dimer levels than patients without medical conditions (z = 2,999, p (sig (2-sided test)) < 0.05). Conclusion: Although they have recovered from Covid-19, there is still a fairly high proportion of survey subjects with D-dimer levels higher than the normal threshold, posing a potential risk of hemostatic disorders in post Covid-19 patients. In addition, the study also showed that the group of subjects with abnormal D-dimer concentrations was related to factors such as female gender, age ≥ 60 and comorbidities. Therefore, it is necessary to periodically monitor and screen post Covid-19 people, especially in high-risk groups.